Cardiac fibroblasts and mechanosensation in heart development, health and disease - Pesce, Maurizio; Duda, Georg N; Forte, Giancarlo; Girao, Henrique; Raya, Angel; Roca-Cusachs, Pere; Sluijter, Joost P G; Tschöpe, Carsten; Van Linthout, Sophie (Nature reviews cardiology, 2023)
The term 'mechanosensation' describes the capacity of cells to translate mechanical stimuli into the coordinated regulation of intracellular signals, cellular function, gene expression and epigenetic programming. This capacity is related not only to the sensitivity of the cells to tissue motion, but also to the decryption of tissue geometric arrangement and mechanical properties. The cardiac stroma, composed of fibroblasts, has been historically considered a mechanically passive component of the heart. However, the latest research suggests that the mechanical functions of these cells are an active and necessary component of the developmental biology programme of the heart that is involved in myocardial growth and homeostasis, and a crucial determinant of cardiac repair and disease. In this Review, we discuss the general concept of cell mechanosensation and force generation as potent regulators in heart development and pathology, and describe the integration of mechanical and biohumoral pathways predisposing the heart to fibrosis and failure. Next, we address the use of 3D culture systems to integrate tissue mechanics to mimic cardiac remodelling. Finally, we highlight the potential of mechanotherapeutic strategies, including pharmacological treatment and device-mediated left ventricular unloading, to reverse remodelling in the failing heart.
Keywords: srdeční komory; Heart Failure; Ventricular Remodeling; Myocardium; Heart Ventricles; fibroblasty; lidé; srdeční selhání; Fibroblasts; remodelace komor; myokard; Humans